Microalgae for Palm Oil Mill Effluent (POME) Remediation: Future Trends - Mohd Azmil, Nurlydia; Yuzir, Ali; Mohamad, Shaza Eva; Abdullah, Norhayati; El Sheekh, Mostafa (Tecno Scientifica Publishing, 2025)
Microalgae-based remediation of palm oil mill effluent (POME) grew rapidly, yet evidence remained dispersed across methods and outcomes. This study undertook bibliometric mapping to organise research growth, thematic structure, and actionable pathways aligned with SDGs 6, 7, 12, and 14. A Scopus database of 124 articles (2008–2025) was analysed with VOSviewer to produce keyword co-occurrence and temporal overlays, complemented by impact indicators and close reading of highly cited studies. Output increased from a formative phase to a peak in 2021, with 3275 citations overall and influence that was concentrated yet broad (h = 35; g = 51; m = 1.944). The network resolved into a central focal point (POME, microalgae, effluent/wastewater), surrounded by two related fields: pollutant metrics (COD, nitrogen, phosphorus), which supported treatment claims, and valorisation (biomass, lipid, biofuel), which linked remediation to product streams. Temporal overlays showed a progression from feasibility and nutrient polishing to method-rich optimisation (kinetics, immobilisation) and, more recently, to cultivation realism, phycoremediation, and sustainability. These patterns indicated practical levers for mill-scale deployment, including on-site cultivation with boiler CO₂, microalgae–bacteria partnerships for robustness, and combined pond–photobioreactor systems that balanced cost and control. Together, these combinations delivered cleaner effluents (SDG 6), low-carbon energy vectors (SDG 7), circular nutrient and residue reuse (SDG 12), and reduced land-based marine pollution (SDG 14). Remaining priorities included harmonised reporting of removals and yields, techno-economic and life cycle assessments at mill cluster scale, resilient process control and safety for multi-stage systems, and biomass quality assurance to safeguard downstream uses.